Nature writings - Muir, John 1838-1914 (New York : The Library of America, 1997)
The story of my boyhood and youth.
My first summer in the Sierra.
The mountains of California.
Stickeen.
Selected essays.
Contenido : <The story of my boyhood and youth> <My first summer in the Sierra> <The mountains of California> <Stickeen> <Selected essays>
Keywords: ESTADOS UNIDOS; LITERATURA AMERICANA USA; NOVELA; ENSAYO; CAJA 3